1997
DOI: 10.1118/1.598111
|View full text |Cite
|
Sign up to set email alerts
|

Calculating output factors for photon beam radiotherapy using a convolution/superposition method based on a dual source photon beam model

Abstract: A realistic photon beam model based on Monte Carlo simulation of clinical linear accelerators was implemented in a convolution/superposition dose calculation algorithm. A primary and an extra-focal sources were used in this beam model to represent the direct photons from the target and the scattered photons from other head structures, respectively. The effect of the finite size of the extra-focal source was modeled by a convolution of the source fluence distribution with the collimator aperture function. Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…More complex dual source photon beam models reached an agreement within 1% between calculated and measured output factors in water ͑different reference conditions and energies͒. 32,39 No beam model yielded a significant deviation compared to the full MC model because of its relatively large standard deviations. However, the models 1 and 2 led to significant deviations compared to the measurements for all field sizes greater than 15ϫ15 cm 2 , and model 3 only for the field sizes of 15 ϫ15 cm 2 and 40ϫ40 cm 2 .…”
Section: Resultsmentioning
confidence: 84%
“…More complex dual source photon beam models reached an agreement within 1% between calculated and measured output factors in water ͑different reference conditions and energies͒. 32,39 No beam model yielded a significant deviation compared to the full MC model because of its relatively large standard deviations. However, the models 1 and 2 led to significant deviations compared to the measurements for all field sizes greater than 15ϫ15 cm 2 , and model 3 only for the field sizes of 15 ϫ15 cm 2 and 40ϫ40 cm 2 .…”
Section: Resultsmentioning
confidence: 84%
“…the S cb (x,y) obtained from the Monte Carlo simulation was also compared to the measured data based on counting the electronic feedback pulses or accumulative charge from the electron target. 1,11 To evaluate the effect of the backscatter on treatment fields using jaw movement, S cp (x,y) was also calculated for treatment fields using dynamic wedges.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work, 1 we showed that the change of photon output as a function of field geometry is essentially caused by three factors: the head scatter, the phantom scatter, and the backscattered radiation from collimator jaws into monitor chambers. We developed a convolution/superposition algorithm to compute the photon output or dose per monitor unit.…”
Section: Introductionmentioning
confidence: 99%
“…IMRT techniques 4,5 ). High dose gradients are common to all of these stereotactically guided irradiation fields, regardless of their shape, thus precise algorithms are required having to be verified in terms of precise dosimetric measurements [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%